Development of a Ni-Ce0.8Zr0.2O2 catalyst for solid oxide fuel cells operating on ethanol through internal reforming - Liao, M.; Wang, W.; Ran, R.; Shao, Zongping (2011)
Inexpensive 20 wt.% Ni-Ce0.8Zr0.2O2 catalysts are synthesized by a glycine nitrate process (GNP) and an impregnation process (IMP). The catalytic activity for ethanol steam reforming (ESR) at 400-650 °C, catalytic stability and carbon deposition properties are investigated. Ni-Ce0.8Zr0.2O2 (GNP) shows a higher catalytic performance than Ni-Ce0.8Zr0.2O 2 (IMP), especially at lower temperatures. It also presents a better coking resistance and a lower graphitization degree of the deposited carbon. The superior catalytic activity and coke resistance of Ni-Ce0.8Zr 0.2O2 (GNP) is attributed to the small particle size of the active metallic nickel phase and the strong interaction between the nickel and the Ce0.8Zr0.2O2 support, as evidenced by the XRD and H2-TPR. The Ni-Ce0.8Zr0.2O 2 (GNP) is further applied as an anode functional layer in solid oxide fuel cells operating on ethanol steam. The cell yields a peak power density of 536 mW cm-2 at 700 °C when operating on EtOH-H 2O gas mixtures, which is only slightly lower than that of hydrogen fuel, whereas the cell without the functional layer failed for short-term operations. Ni-Ce0.8Zr0.2O2 (GNP) is promising as an active and highly coking-resistant catalyst layer for solid-oxide fuel cells operating on ethanol steam fuel. © 2011 Elsevier B.V. All rights reserved.